COMPARISON AMONG THREE TECHNIQUES IN THE PARASITOLOGICAL DIAGNOSIS OF Fasciola hepatica IN CATTLE - Dias, Anderson Silva; Araújo, Jackson Victor de; Braga, Fábio Ribeiro; Calian, Odilon Azevêdo; Vilela, Vinícius Longo Ribeiro; Miranda, Vinícius Zacarias (Archives of Veterinary Science, 2014)
<span style="font-size: 12.0pt; font-family: Arial; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">Helminthosis are relevant because they are responsible by substantial economic losses. Many techniques have been developed to facilitate parasitological diagnosis and comparisons among these techniques are essential. The present work aimed a comparison among three techniques of quantitative sedimentation for parasitological diagnosis of Fasciola hepatica in cattle. The modified sedimentation techniques of Dennis, Stone & Swanson (DSS), Girão and Ueno (quatro tamises - QT; four sieves) and Foreyt were compared using analysis of variance, linear regression and correlation tests. Evaluations of sensitivity, specificity and agreement were performed using the kappa test. It was found that the modified DSS technique had a high mean egg count and high sensitivity (p<0.01) (48.60%). The three techniques showed a specificity of 100%. There was no correlation among the values of egg count obtained by the three techniques, and significant coefficients were not observed by regression analysis. The egg count results of F. hepatica obtained by the techniques of quatro tamises and Foreyt showed excellent concordance by the kappa test. The modified DSS technique appeared to be the most effective for F. hepatica diagnosis in cattle (p<0.01).